Diagnostic challenges in pediatric arthritis: A case of systemic juvenile idiopathic arthritis misdiagnosed as septic arthritis in a 3-year-old boy - Sogol Alesaeidi; Mohsen Jari (SAGE Open Medical Case Reports)
Arthritis in children has several causes, including infectious, inflammatory, and infiltration of malignant cells, and it is important to differentiate them as soon as possible. We present the case of a 3-year-old boy who was initially diagnosed with septic arthritis secondary to joint pain, swelling, and high fever. Despite appropriate antibiotic therapy, the patient’s symptoms persisted, leading to an eventual diagnosis of systemic juvenile idiopathic arthritis (sJIA). This case highlights the importance of distinguishing between septic arthritis and sJIA because early misdiagnosis can lead to delayed treatment and potential complications.